Summary Report Comparing High Voltage Overhead and Underground Transmission Infrastructure - Madigan, Gary; Lee, Colin; Cetois, Audrey; Dixit, Anupam; Zhong, Xin; Knight, Andrew; Rohl, Sarah; Aghamohammadi, Nasrin; Saha, Tapan; Ackermann, Fran; Ashworth, Peta (Curtin University and University of Queensland, 2023)
This report summarises the findings of an independent systematic literature review of high voltage overhead and underground transmission infrastructure, which was undertaken by The University of Queensland and Curtin University. This is the summary report for the study which is complemented by more detailed reports provided separately in Chapters 1 to 8 which cover the themes and cases studies in more detail.